2012
DOI: 10.1111/acps.12033
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of mindfulness‐based cognitive therapy for bipolar disorder

Abstract: A randomized controlled trial of mindfulness-based cognitive therapy for bipolar disorder.Objective: To compare the efficacy of mindfulness-based cognitive therapy (MBCT) plus treatment as usual (TAU) to TAU alone for patients with bipolar disorder over a 12-month follow-up period. Method: Participants with a DSM-IV diagnosis of bipolar disorder were randomly allocated to either MBCT plus TAU or TAU alone. Primary outcome measures were time to recurrence of a DSM-IV major depressive, hypomanic or manic episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 40 publications
5
121
0
5
Order By: Relevance
“…The lack of significant improvement among women with BSD contrasts with results from open trials that have found positive effects of MBCT on depression or anxiety symptoms in bipolar disorder (Weber et al 2010;Miklowitz et al 2009;Deckersbach et al 2012;Ives-Deliperi et al 2013;Williams et al 2008). Our findings are, however, consistent with the single randomized trial of adults with bipolar disorder that found no effects of MBCT compared to usual care on depression or hypomania symptoms over 12-months (Perich et al 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lack of significant improvement among women with BSD contrasts with results from open trials that have found positive effects of MBCT on depression or anxiety symptoms in bipolar disorder (Weber et al 2010;Miklowitz et al 2009;Deckersbach et al 2012;Ives-Deliperi et al 2013;Williams et al 2008). Our findings are, however, consistent with the single randomized trial of adults with bipolar disorder that found no effects of MBCT compared to usual care on depression or hypomania symptoms over 12-months (Perich et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Several other open trials of MBCT have reported effects on depression or anxiety symptoms in patients with bipolar I or II disorder over 3 months (Deckersbach et al 2012;Williams et al 2008). The only randomized trial of MBCT in bipolar disorder, however, showed no significant benefit of the classes compared to usual care on depression or hypomania symptoms over 12-months (Perich et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…One RCT of MBCT involving 95 patients did not demonstrate any difference in relapse prevention compared to a treatment‐as‐usual group, but did reveal fewer anxiety and depressive symptoms in the MBCT arm 115. Coupled with the findings of other smaller studies, this suggests that MBCT may have a role to play in anxiety reduction in BD 75, 116…”
Section: Foundations Of Managementmentioning
confidence: 86%
“…Specifically for bipolar disorder, CBT trial results have been characterized as "mixed" and suggest the need for potential schematic changes in therapeutic intervention (Perich, Manicavasagar, Mitchell, Ball, & Hadzi-Pavlovic, 2013). …”
mentioning
confidence: 99%